The Regularities of Electrolytic Dissociation of Weak Dibasic and Tribasic Organic Wine Acids - Kvaratskhelia, E.; Kvaratskhelia, R.; Kurtanidze, R. (Journal of Applied Solution Chemistry and Modeling, 2013)
The weak dibasic and tribasic organic acids in wine: tartaric, malic, citric and succinic acids are the important components having direct influence on various properties of wine. The regularities of electrolytic dissociation of these acids determine all their useful properties. With the aid of suggested by authors original method for analysis the complex equilibria of the processes of dissociation of weak multibasic organic acids the main dissociation parameters of tartaric, malic, citric and succinic acids in their dilute solutions: the values of usual and â€œpartialâ€ degrees of dissociation of all steps, the concentrations of all anions, hydrogen ions and undissociated acid molecules are determined. The concentration intervals of predominance of various charged and uncharged substances in dilute solutions of all above mentioned acids are also determined. The simple empirical equations for fast approximate calculation of the dissociation degrees and pH values are also suggested.